Proteasome Inhibition Activates Autophagy-Lysosome Pathway Associated With TFEB Dephosphorylation and Nuclear Translocation - Li, Chunyan; Wang, Xin; Li, Xuezhi; Qiu, Kaixin; Jiao, Fengjuan; Liu, Yidan; Kong, Qingxia; Liu, Yan; Wu, Yili (Frontiers in Cell and Developmental Biology, 2019)
Ubiquitin-proteasome pathway (UPS) and autophagy-lysosome pathway (ALP) are the two major protein degradation pathways, which are critical for proteostasis. Growing evidence indicates that proteasome inhibition-induced ALP activation is an adaptive response. Transcription Factor EB (TFEB) is a master regulator of ALP. However, the characteristics of TFEB and its role in proteasome inhibition-induced ALP activation are not fully investigated. Here we reported that the half-life of TFEB is around 13.5 hours in neuronal-like cells, and TFEB is degraded through proteasome pathway in both neuronal-like and non-neuronal cells. Moreover, proteasome impairment not only promotes TFEB accumulation but also facilitates its dephosphorylation and nuclear translocation. In addition, proteasome inhibition-induced TFEB accumulation, dephosphorylation and nuclear translocation significantly increases the expression of a number of TFEB downstream genes involved in ALP activation, including microtubule-associated protein 1B light chain-3 (LC3), particularly LC3-II, cathepsin D and lysosomal-associated membrane protein 1 (LAMP1). Furthermore, we demonstrated that proteasome inhibition increases autophagosome biogenesis but not impairs autophagic flux. Our study advances the understanding of features of TFEB and indicates that TFEB might be a key mediator of proteasome impairment-induced ALP activation.